(untitled) (Homoeopathy for All, 2021)
COMMONLY REFERRED to as “PILES”, haemorrhoids are distended veins in the lining of the anus. This condition is common and is often attributed to a low-fiber diet and an inadequate intake of fluid. Straining to pass small, hard stools increases the pressure in the abdomen, which slows the flow of blood in the veins around the anus. Repeated straining produces the distended veins known as piles.